Transformation of Traditional Values in the Tolaki Tribe’s Local Wisdom-Based Education System at Elementary School Level - Maharani, Diva; Putri, Noni (Cendekiawan : Jurnal Pendidikan dan Studi Keislaman, 2024)
This study examines the transformation of traditional Tolaki values in a local wisdom-based education system at the elementary school/Islamic elementary school level amidst the challenges of globalization and educational standardization in Indonesia. Through a critical ethnographic approach in five elementary schools with 15 key informants, this study identified five Tolaki values relevant to contemporary elementary education: Medulu Mepoko'aso (unity), Morini Mbu'umbundi (hard work), Samaturu (mutual cooperation), Kalosara (conflict resolution), and Kohanu (integrity). Three implementation patterns were found: symbolic (45%), content (32%), and integrated (23%). An effective transformation model that includes curriculum revitalization, capacity building of elementary school/Islamic elementary school teachers, community involvement, and value-based evaluation shows a significant improvement in the character formation of elementary school/Islamic elementary school students, especially in the aspects of cooperation, responsibility, integrity, and respect for cultural identity. This study concludes that the transformation of traditional values at the elementary school/Islamic elementary school level is not only an effort to preserve culture, but also a strategy to create character education that is contextual and relevant to global and local needs.